What will we find when we turn the page? : theorizing a more expansive notion of transitional justice (2020)
In its search to promote accountability and remedy large-scale, systematic human rights violations, the field of transitional justice has largely overlooked violations of economic, social, and cultural (ESC) rights. However, these violations are at the heart of many conflicts and addressing them is critical to one of transitional justice's aims: non-repetition. This article asks why transitional justice theory has largely focused on civil and political rights and argues theory should be informed by praxis, which as cases like Colombia show, is progressively integrating ESC rights and transitional justice in measures like comprehensive reparations and rural reforms. Transitional justice is a living concept, and as such, where relevant it should be cognizant of all violations perpetrated to better turn the page on conflict.